Klasik Sosyolojinin Şarkiyatçı Kaynakları: Marx ve Weber’in Karşılaştırmalı Bir İncelemesi (Orientalist Sources of Classical Sociology: A Comparative Analysis of Marx and Weber) - Lütfi Sunar (İnsan & Toplum)
Sociology emerged as a comparative science, which basically tries to find out the differences between societies. Hence, it is important to make comparisons with Oriental societies that may serve as a historical model and situate the forms of modern society with regard to them. In this process, sociology has provided new explanations for European societies through working on the information gathered by orientalists. Therefore, the development and transformation of orientalism have also led to the transformation of sociology. This transformation can clearly be seen through a comparative examination of the approaches, analysis, and sources of Marx and Weber, who supposed to represent opposite poles in sociology. In the mid-19th century while orientalism was at the developmental stage, Marx made broad generalization with limited analysis. When oriental studies became specialized and diverse in the early 20th century, Weber made more extensive comparisons supported by detailed analysis. Despite the epistemological and political differences between Marx and Weber, they were of the same mind in their interpretations of modern society through Oriental societies and their unquestioning use of orientalist sources.